Guinea : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Nonobservance of Performance Criteria, Modification of Performance Criteria, Augmentation of Access, and Financing Assurances Review; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the First Review Under the Poverty Reduction and Growth Facility (PRGF) for Guinea. All but two quantitative performance criteria (PC) were met. IMF staff supports the authorities' requests for waivers of nonobservance, based on their remedial actions. Progress of structural reforms was broadly satisfactory and all structural PCs and benchmarks for end-December 2007 were met. However, several quantitative indicative targets for end-March 2008 were missed, in part on account of a delayed response to the financial pressures arising from higher fuel prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet